2020
DOI: 10.4103/ajns.ajns_309_20
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic cerebellar hematoma: A tertiary care experience of 23 conservatively managed cases

Abstract: Context: Traumatic cerebellar hematomas are rare in comparison to nontraumatic cerebellar hematomas. Aims: The aim of this study is to evaluate the prognostic factors and outcome determining factors with regard to conservatively managed isolated traumatic cerebellar hematoma. Settings and Design: Retrospective cohort study. Materials and Methods: A retrospective study of 23 patients of conservatively managed isolat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(16 citation statements)
references
References 15 publications
1
15
0
Order By: Relevance
“…Traumatic cerebellar contusions and hematomas are relatively uncommon. [ 15 ] When they do occur, they become risk factors for developing hydrocephalus, often due to the compression of posterior fossa CSF structures. The posterior fossa is a small intracranial compartment compared to the anterior and middle cranial fossa,[ 3 ] which makes compression of the fourth ventricle or cerebral aqueduct an established risk.…”
Section: Discussionmentioning
confidence: 99%
“…Traumatic cerebellar contusions and hematomas are relatively uncommon. [ 15 ] When they do occur, they become risk factors for developing hydrocephalus, often due to the compression of posterior fossa CSF structures. The posterior fossa is a small intracranial compartment compared to the anterior and middle cranial fossa,[ 3 ] which makes compression of the fourth ventricle or cerebral aqueduct an established risk.…”
Section: Discussionmentioning
confidence: 99%
“…[ 17 , 18 ] Despite their relative rarity, cerebellar contusions are associated with substantial morbidity and mortality, with estimates of poor clinical outcomes ranging between 20% and 100%, with an average of 60%. [ 1 , 5 , 8 , 14 , 15 ] These injuries result in a myriad of long-term sequelae that have a significant impact on patients’ quality of life, including the resultant development of deficits in speech, attention, and fine motor movement. [ 15 ] Due to their relative rarity, the existing literature is limited on the factors predicting and influencing the clinical picture and long-term outcomes of patients sustaining cerebellar contusions.…”
Section: Introductionmentioning
confidence: 99%
“…[ 15 ] Due to their relative rarity, the existing literature is limited on the factors predicting and influencing the clinical picture and long-term outcomes of patients sustaining cerebellar contusions. [ 1 , 14 ] Previous studies have demonstrated that the best indicator of outcomes following cerebellar contusions is the patients’ Glasgow Coma Scale (GCS) scores on admission. Other prognostic factors include effacement of the basal cisterns, 4 th ventricular compression, intraventricular hemorrhage, the size and location of the contusion, concomitant subarachnoid hemorrhage (SAH), and the presence of associated cerebral injury.…”
Section: Introductionmentioning
confidence: 99%
“…During the last decade, minimally invasive surgery has gained wide acceptance and popularity due to its excellent outcome and clinical results. In neurosurgery, the endoscopic third ventriculostomy (ETV) is universally performed for the treatment of primary and secondary hydrocephalus and its indications are broader every day [1].…”
Section: Introductionmentioning
confidence: 99%
“…Traumatic cerebellar hematomas or hemorrhagic contusions are rare in comparison to nontraumatic causes and may present acutely or in a delayed fashion when they are referred to as delayed traumatic intracerebellar hematoma [1].…”
Section: Introductionmentioning
confidence: 99%